Sural flap for tissue loss of the hindfoot in the diabetic - Assi, Chahine (2011)
The purpose of this retrospective study was to evaluate the reliability of the sural flap with a distal pedicle for covering tissue loss of the posterior aspect of the heal and the malleolar region in diabetic patients. We present a retrospective consecutive series with 28 month follow-up. Thirteen flaps in 13 patients (10 men, 3 women), mean age 64 years. A homolateral flap was used in all cases, covering on average 48 cm2. Substance loss involved the hind foot in ten cases and the malleolar region in three. Three patients had recent bone trauma, four had chronic osteitis and six a pressure wound involving the heel. All patients had non-insulin dependent diabetes mellitus. The flap head in 24 days on average (range 18–45), the donor site in 15 days. Eleven patients were able to wear normal shoes. At last follow-up all patients were free of infectious recurrence. There was one flap necrosis, three necrotic borders (one skin graft), two cases of venous insufficiency, and ten cases of hypoesthesia of the lateral border of the foot. There have not been any reports in the literature of the neurocutaneous sural flap with a distal pedicle for diabetic patients. In our series, this flap was found to be a reproducible solution for covering substance loss of the heel and malleolar region in the diabetic. This flap with a long pedicle does not require microvascular qualification. It is easy to perform, induces few functional sequelae. For diabetic patients, it is an alternative to amputation, without compromising future options since the vascular and muscle stock are preserved.